Peran Oposisi sebagai Cheks and Balance dalam Sistem Politik Demokrasi di Indonesia - Sukarno, Bedjo - (Joglo, 2011)
A group of people or political parties to put my self in his position as an opposition which has a strong enough legal basis to criticize and supervise the strict policies of the ruling government's policies. In an effort to play an opposition role, contributing ideas for the creation of a clean government and the realization of the political system and democratic political behavior. Keyword: Role of cheks and balance, a democratic political system Â